Mehmet Rauf's Novel September: One of the first psychological novels written under the influence of Western literature and its critical analysis - Shorena Gezgic Sultanishvili (European Scientific Journal, ESJ, 2025)
The scientific article aims to analyze the factors provoking betrayal and the origin of remorse and to present psychological portraits of the characters in Mehmed Rauf's acclaimed novel September. As some literary critics suggest, it is considered to be the first psychological novel in Turkish literature of the Servet-i-Funun period. The novel is written under the influence of literary tendencies dominant in that period. Therefore, the theoretical framework chosen for the analysis of the novel is Naturalism and Experimental Realism, which addresses different aspects of human lives, such as history, culture and social class. The novel bears clear features of Naturalism, such as objectivism, and a discrete description of characters and societies. The article applies the method of content analysis and critical study of the scientific literature related to the novel itself and the analysis of new tendencies in Turkish literature. Based directly on the novel's text, the article studies the reasons and the source of elusive marital infidelity, its impact on the characters, and the tormenting feelings caused by remorse. New psychological motives that appear in the novel September could be considered as an original phenomenon in Turkish literature in the period around 1900; Though the end of the novel is tragic, the characters of September are forgiven for their “misdeeds” as the death of the main hero purifies their sins.